Progress in plasma wakefield acceleration driven by a short intense bunch of relativistic electrons - Onishchenko, I.N. (Вопросы атомной науки и техники, 2006)
The recent experimental results on frontier values of accelerating gradient and energy gain achieved by advanced acceleration
methods based on intense plasma wakefields driven by a high-power short laser pulse or a large charge electron
bunch are overviewed. Physical principles are considered for high-gradient acceleration of charged particles with
purpose to elaborate the concept of future compact accelerators, which are called for high-energy physics and high technology
applications, and also for creation of contemporary short pulsed radiation sources. The results of investigations
on laser plasma wakefield accelerator (LWFA) generating precise monoenergtic beams with a small angle divergence
and on plasma wakefield accelerator (PWFA) achieving breakdown through GeV barrier energy gain at SLAC by use
wakefield excited by a short intense electron bunch in 1 m length plasma are presented. The possibility of PWFA application
to doubling the energy of a future linear collider without doubling its length is considered. Представлены последние экспериментальные результаты по получению высоких ускоряющих градиентов и достигнутых максимальных энергий в новых методах ускорения, основанных на интенсивных кильватерных полях, возбуждаемых в плазме мощным коротким лазерным импульсом или электронным сгустком с большим зарядом. Представлені останні експериментальні результати по отриманню високих прискорюючих градієнтів і досягнутих максимальних енергій в нових методах прискорення, заснованих на інтенсивних кільватерних полях, збуджених у плазмі потужним коротким лазерним імпульсом або електронним згустком з великим зарядом